Stronger together: learning from an interdisciplinary Dementia, Arts & Wellbeing Network (DA&WN) - Tischler, Victoria; Schneider, Justine; Morgner, C.; Crawford, Paul; Dening, Tom; Brooker, Dawn; Garabedian, Claire; Myers, T.; Early, F.; Shaughnessy, N.; Innes, Anthea; Duncan, K.; et al. (Taylor and Francis, 2018)
There is increasing interest in the use of arts and creative activity to enhance dementia care (e.g. Beard, 2012; Cowl & Gaugler, 2014; Young, Camic & Tischler, 2016), and to bring together and support professionals and those who use services, see Creative Practice as Mutual Recovery (2018). Over the past decade a growing body of research has established this interdisciplinary field of study and there are strategic moves to embed the arts in healthcare more widely (All-Party Parliamentary Group for Arts, Health and Wellbeing, 2017). However, existing research and arts practice have often proceeded in parallel with practitioners criticised for not providing evidence of efficacy, and researchers berated for not working collaboratively with artists (Zeilig & West, in press) and not involving people living with dementia in the co-design of research.